Relevansi Misi Allah dalam Gereja Katolik Berdasarkan Tinjauan Injil Yohanes 3:16 - Solosumantro, Heribertus; Suriyanto, Eduardus (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
This article aims to express a view about God's mission based on a study of the text of the Holy Bible and a study of the teachings of the Catholic Church. The text of the Holy Bible is a guide to the life of God's people in the Catholic Church, because the text expresses various meanings and values of life that are usually criticized and practiced in the life of faith of a community. The method used in this paper is a qualitative method with a hermeneutic approach. The three points of relevance that the author found in this article are findings that strengthen the roots of the faith and spiritual life of God's people in the Catholic Church. The three points include; social solidarity, the spirit of sacrificing boundaries without the people of God in the Catholic Church and total self-surrender. The third point of relevance of God's Mission in the lives of God's people in the Catholic Church is a strengthening of the meaning and practice of a life of faith that upholds the goodness of living together (bonum Communae).